2019
DOI: 10.3390/app9163313
|View full text |Cite
|
Sign up to set email alerts
|

A Business Process Analysis Methodology Based on Process Mining for Complaint Handling Service Processes

Abstract: To improve the service quality of complaint handling service in a manufacturing company, it is key to analyze the business processes. Process mining is quite a useful approach to diagnose complaint handling service process problems, such as bottlenecks and deviations. However, the current business process analysis methodologies based on process mining mainly focus on operational process analysis and neglect other system level analysis. In this study, we introduce the method of Accimap from the discipline of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This would measure the generalizability of this research, and make it possible to enhance it, wherever the room for improvement can be found. Finally, employing a business process analysis methodology such as process mining may prove to be a useful approach to help determine data mining goals through the identification of an organization's bottlenecks and deviations [37].…”
Section: Discussionmentioning
confidence: 99%
“…This would measure the generalizability of this research, and make it possible to enhance it, wherever the room for improvement can be found. Finally, employing a business process analysis methodology such as process mining may prove to be a useful approach to help determine data mining goals through the identification of an organization's bottlenecks and deviations [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a case study method enables to develop a better insight into a complex and relatively unexplored phenomenon [59]. In particular, in the area of applied industrial technologies this research methodology as proven to be a valid way to study a vast range of topics such as assembly line design [60], product innovation [61], product service design [62] and business process analysis [63].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they implemented these strategies and tested them in both business-like event logs, as recorded in a higher educational enterprise resource planning system, and a real case scenario involving a set of Dutch municipalities. − In [23], the authors introduced the method of Accimap from the discipline of accident analysis to analyze the diagnosis results of process mining by creating a complaint handling service process management Accimap model and using it across different system levels.…”
Section: Related Workmentioning
confidence: 99%
“…The behavioral sequence (BS) analysis results on the Experimental Dataset-2. ,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43 …”
mentioning
confidence: 99%